Survival of neonates in rural Southern Tanzania: does place of delivery or continuum of care matter? - Nathan Rose; Mwanyangala Mathew (BMC, 2012)
Abstract Background The concept of continuum of care has recently been highlighted as a core principle of maternal, newborn and child health initiatives, and as a means to save lives. However, evidence has consistently revealed that access to care during and post delivery (intra and postpartum) remains a challenge in the continuum of care framework. In places where skilled delivery assistance is exclusively available in health facilities, access to health facilities is critical to the survival of the mother and her newborn. However, little is known about the association of place of delivery and survival of neonates. This paper uses longitudinal data generated in a Health and Demographic Surveillance System in rural Southern Tanzania to assess associations of neonatal mortality and place of delivery. Methods Three cohorts of singleton births (born 2005, 2006 and 2007) were each followed up from birth to 28 days. Place of birth was classified as either "health facility" or "community". Neonatal mortality rates were produced for each year and by place of birth. Poisson regression was used to estimate crude relative risks of neonatal death by place of birth. Adjusted ratios were derived by controlling for maternal age, birth order, maternal schooling, sex of the child and wealth status of the maternal household. Results Neonatal mortality for health facility singleton deliveries in 2005 was 32.3 per 1000 live births while for those born in the community it was 29.7 per 1000 live births. In 2006, neonatal mortality rates were 28.9 and 26.9 per 1,000 live births for deliveries in health facilities and in the community respectively. In 2007 neonatal mortality rates were 33.2 and 27.0 per 1,000 live births for those born in health facilities and in the community respectively. Neonates born in a health facility had similar chances of dying as those born in the community in all the three years of study. Adjusted relative risks (ARR) for neonatal death born in a health facility in 2005, 2006 and 2007 were 0.99 (95%CI: 0.58 - 1.70), 0.98 (95%CI: 0.62 - 1.54) and 1.18 (95% CI: 0.76 - 1.85) respectively. Conclusions We found no evidence to suggest that delivery in health facilities was associated with better survival chances of the neonates.